A influência dos fatores contingenciais nas práticas do sistema de controle gerencial sob a perspectiva dos princípios globais de contabilidade gerencial: um estudo empírico no setor industrial - Siqueira, Diego Dantas (2021)
It has been argued that the decision process had never been so important (or complex) in so far as there is an increase in the amount of unstructured information, a competitive environment increasingly hostile, changes in the behavior of the purchasing of consumers and frequent innovations (CGMA, 2014). In this context, the Global Management Accounting Principles (GMAP) were proposed to be an auxiliary for managers from different companies to benchmark and improve their Management Control System (MCS), improving provided information and, therefore, decision making. In this way, using the contingency theory as a theoretical framework, this study aimed to analyze the influences of contingency factors on the practices of the management control system from the perspective of the GMAP, and the latter on the organizational performance of the Paraiba industries. To this end, a survey was conducted through the application of a questionnaire with those responsible for the sector of controllership/management accounting of Paraiba industries registered with the Federation of Industries of the State of Paraiba (FIEP) in 2020. This resulted in 86 valid observations. Data was analyzed by a Spearman correlation test and structural equation modeling. The results permitted to accept four out of the six raised in this study, ratifying the influence of (i) environment insurance, (ii), structure, (iii) technology on the practices of the organization's management control system, and the latter on (iv) organizational performance. These results indicate that MCS with GMAP related practices is affected by the contingency variables experienced by the companies, and that companies which use these practices in their MCS have the possibility of increasing their performance. Finally, no evidence was found that (v) strategy and (vi) organizational size influence the practices of the organization's management control system. This research contributes to the literature by analyzing MCS under a new perspective (from GMAP). Few has been done in accounting research in the sense of identifying the factors that can contribute to the adoption of an efficient MCS, in light of the GMAP structure guidelines. In practical terms, these results can be useful as they provide empirical evidence that the MCS with practices related to the GMAP should not be applied equally in different organizations.